2019
DOI: 10.1002/adma.201905661
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Bifacial Passivation with Crosslinked Thioctic Acid for High‐Performance Methylammonium Lead Iodide Perovskite Solar Cells

Abstract: Organic-inorganic hybrid halide perovskite materials have been used in optoelectronic applications, including photodetectors, X-ray imaging, lasing, photocatalysis, lightemitting diodes, and so on. [1][2][3][4][5] Owing to their high optical absorption coefficient, low exciton binding energy, long charge carrier diffusion lengths, high photoluminescence (PL) quantum yield, suitable bandgap, and energy level, perovskite solar cells (PSCs) are emerging as promising candidates for the next-generation thin-film so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
151
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(157 citation statements)
references
References 50 publications
5
151
0
1
Order By: Relevance
“…[ 17 ] Moreover, previously reported work indicated that trap states mainly located at the interfaces of multilayers of whole device (called interface defects) and at the perovskite surface (called surface defects), which are effectively related to the energy level matching, hysteresis, charge carriers dynamics, and the long‐term environmental and operational stability. [ 18–22 ] Therefore, it is indispensable to explore an impressive way to diminish the defects, particularly at the interfaces, for acquiring the high‐efficient and stable PSCs. Currently, there are lots of approaches to improve the performance and stability of PSCs, containing additive engineering, using additive into a perovskite absorber layer and interface engineering, modifying the hole transport layer (HTL)/perovskite or perovskite/electron transport layer (ETL) interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…[ 17 ] Moreover, previously reported work indicated that trap states mainly located at the interfaces of multilayers of whole device (called interface defects) and at the perovskite surface (called surface defects), which are effectively related to the energy level matching, hysteresis, charge carriers dynamics, and the long‐term environmental and operational stability. [ 18–22 ] Therefore, it is indispensable to explore an impressive way to diminish the defects, particularly at the interfaces, for acquiring the high‐efficient and stable PSCs. Currently, there are lots of approaches to improve the performance and stability of PSCs, containing additive engineering, using additive into a perovskite absorber layer and interface engineering, modifying the hole transport layer (HTL)/perovskite or perovskite/electron transport layer (ETL) interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…[ 126 ] As shown in Figure a, the crosslinkable thioctic acid (TA) can in situ crosslinked to form a polymer (poly(TA)) network after thermal treatment, effectively passivate defects in the perovskite film. [ 122 ] Moreover, the —COOH group in TA can interact with PbI 2 and TA is chemically bonded to GBs. Therefore, the finally prepared PSCs show negligible hysteresis benefit from the low defect density in the perovskite film.…”
Section: Methods Of Reducing or Eliminating Hysteresismentioning
confidence: 99%
“…Reproduced with permission. [ 122 ] Copyright 2020, Wiley‐VCH Publications. b) Molecular structure of DMF, GBL, NMP, and DMSO.…”
Section: Methods Of Reducing or Eliminating Hysteresismentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the key factors influencing the overall device efficiency should be: 1) the film quality of all functional layers, especially for light absorber and charge transport layers (CTLs); 2) optoelectronic properties of CTLs, such as bandgaps, carrier mobility, and energy levels. [ 20–23 ] Therefore, obtaining high‐quality perovskite film with reduced defects is the prerequisite for high‐performance solar cells. Thus, far ion doping, such as Eu 2+ , [ 24 ] Mn 2+ , [ 25 ] Nb 5+ , [ 26 ] Cu 2+ , [ 27 ] Cl − , [ 25 ] and Br − , [ 28 ] has been proven to be an effective strategy to obtain large grains and in situ strengthen original octahedral structural stability in all‐inorganic perovskite system.…”
Section: Introductionmentioning
confidence: 99%